Dimensions of Consumer Satisfaction By Buying a Mitsubishi Brand Vehicle - Waruwu, Ahmad Aswan; Harianto,; Muda, Iskandar; Soemitra, Andri; Sugianto, (The journal of contemporary issues in business and government, 2021)
PT. New Marwa or Mitsubishi Indonesia Medan branch is engaged in investment in Mitsubishi brand car loans. The problem faced is a decrease in sales turnover. This study aims to determine whether price, product quality, and service quality simultaneously influence consumer satisfaction at Mitsubishi SM Raja Medan. This research uses multiple linear regression models. The distribution of questionnaires to a sample of 91 respondents. The data analysis technique used is the quantitative method with the help of SPSS version 16.0. The results showed that the price partially had a positive and significant effect on consumer satisfaction at Mitsubishi SM Raja. Product quality is partially positive and significant effect on customer satisfaction at Mitsubishi SM Raja. Service quality is partially positive and significant effect on customer satisfaction at Mitsubishi SM Raja. Price, product quality and service quality simultaneously have a positive and significant effect on customer satisfaction at Mitsubishi SM Raja. Adjusted R Square 0.751 or the determination of the remaining 75.1% 24.9% are other factors outside themodel.